Ko-translationale Assemblierung von Proteinkomplexen: Methoden der Proteinforschung - Fenzl, Kai; Kramer, Günter; Bukau, Bernd (Biospektrum, 2021)
The majority of cellular proteins exerts their biological activity as oligomeric complexes. The general view was that complexes form by random collision of folded subunits in the cytosol. Recent studies question this view by demonstrating that a surprisingly high number of complexes are formed during translation. Co-translational assembly occurs by interaction either of fully synthesized subunits with nascent partner subunits, or of two nascent polypeptides exposed by proximal ribosomes.
Gesehen am 26.01.2023